Exploring the use of an under-desk leg swing device during employee aptitude testing and implications on work performance and productivity. - Lam, Hilary; Bergquist, Carter; Lee, Collette; McMullen, Jared (Work, 2023)
BACKGROUND: As modern occupations become more sedentary, desk-bound workers are more at risk of chronic diseases. Active workstations have gained popularity in the workplace, but there remain concerns about their impact on cognitive function. OBJECTIVE: This study investigated the use of a novel under-desk leg swing device on cognitive ability in the workplace compared to sitting. METHODS: Cognitive ability was measured using a pre-employment aptitude test (CCAT), and perceived outcomes were analyzed via self-report questionnaires. Using a randomized, repeated measures crossover design, 18 undergraduate students undertook the CCAT while using the under-desk leg swing device and while sitting only (Experiment 1). 9 students returned two to three weeks later to repeat testing (Experiment 2). RESULTS: In Experiment 1, CCAT scores did not differ significantly between the under-desk leg swing device and sitting (mean difference (MD) = –1.056, standard error (SE) = 1.302,p = 0.429, d = –0.16). Effect sizes of 0.554 were observed for perceived alertness, 0.446 for attention, 0.446 for focus, and 0.564 for enjoyment, but there were no significant differences between the two conditions. CCAT scores were significantly higher in Experiment 2 than in Experiment 1 (MD = 8.444, SE = 2.410,p = 0.008, d = 1.64). CONCLUSION: Based on Experiment 1, the findings suggest that the use of the under-desk leg swing device promotes movement without detriment to neither workflow nor cognitive ability relevant to employee aptitude compared to sitting.